2019
DOI: 10.1016/j.engfracmech.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

On the bonding between glass and PVB in laminated glass

Abstract: In blast protective design, laminated glass is used to facilitate the safety of building occupants. Laminated glass provides its safety through the maintenance of the bond between the glass and the interlayer, and also through the deformation of the interlayer. The amount of deformation is related to the stretching of the interlayer, which is related to the amount of adhesion between the glass and the interlayer. An experimental and modelling study has taken place on the bond between the glass and the interlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Therefore, parallel bond model was also assigned to the interface between glass and PVB. Combined with the current report and our lab tests (Pelfrene et al, 2015;Samieian et al, 2019), the fracture energy via delamination is determined as 1 N/mm in tangential direction and 0.6 N/mm in normal direction. The delamination strength is 8.0 MPa.…”
Section: De Model Of Tct Testmentioning
confidence: 80%
“…Therefore, parallel bond model was also assigned to the interface between glass and PVB. Combined with the current report and our lab tests (Pelfrene et al, 2015;Samieian et al, 2019), the fracture energy via delamination is determined as 1 N/mm in tangential direction and 0.6 N/mm in normal direction. The delamination strength is 8.0 MPa.…”
Section: De Model Of Tct Testmentioning
confidence: 80%
“…where εa is the steady state strain and can then be expressed as εa = δ/a. As one significant property of adhesion, the total surface fracture energy per unit area of interlayer delamination, Gtot, can be calculated by introducing the energy balance approach [30]. It is assumed that the TCT system is without friction, hence, the external work done by the tensile force is equal to the sum of three components: (1) the strain energy stored in the interlayer, (2) energy dissipated to generate interlayer stretch, (3) the work used to increase the delamination depth a by an incremental growth da.…”
Section: Experimental Theory Of Tct Testsmentioning
confidence: 99%
“…It is found that although higher adhesion level increases the energy used to propagate the delamination, the energy dissipated in the stretching of PVB volume is not affected. Samieian et al [30] also adopted TCT test method to study the adhesion of PVB LG in a temperature range of 20 °C to 60 °C. It is observed that the adhesion at constant temperature is load rate dependent whereas that is temperature independent at a constant load rate.…”
Section: Introductionmentioning
confidence: 99%
“…A vast amount of literature is devoted to the evaluation of the mechanical response of sound laminated glass, both theoretically [1][2][3] and experimentally [4][5][6]. Very few works address the post-breakage response.…”
Section: Introductionmentioning
confidence: 99%